A Comparative Study of Bone Marrow Aspiration and Bone Marrow Biopsy in Hematological Diseases - Mainali, Nirajan; Homagai, Neha; Tiwari, Pratap Sagar; Giri, Arun (Journal of Nobel Medical College, 2015)
Introduction: Bone marrow examination is an important diagnostic tool to evaluate various disorder including both neoplastic and non-neoplastic hematological diseases. The two most important techniques used for the diagnosis are bone marrow aspiration and bone marrow trephine biopsy which are complementary to each other.Aim and Objectives: To compare the diagnostic value of bone marrow aspiration and biopsy. Material and methods: A total of 88cases with both bone marrow aspiration and biopsy were included in the study. All the aspirate smears were routinely stained by Jenner Giemsa while the trephine biopsy sections were stained by routine Hematoxylin and Eosin stain.. All the smears and sections were reviewed and the findings on BMA and BMB were compared and the final correlation done.Result: Hypolastic marrow was the most common diagnosis followed by immune thrombocytopenic purpura (ITP). But the diagnostic accuracy of ITP on aspiration was 100 % in compare to hypoplastic marrow (81.25%). The diagnosis accuracy of BMA in our study was 84.09%.Conclusion: Bone marrow aspiration and biopsy complement each other. Bone marrow aspiration provides better study of the cell, whereas biopsy provides detail about the pattern of cellular distribution, hence when performed together it gives better diagnostic accuracy. Journal of Nobel College of Medicine Vol.4(1) 2015: 12-14